Optimization models in layout - Tarazona Bermudez, Giovanny Mauricio; Rodriguez Rojas, Luz Andrea; Ochoa Rodriguez, Julio Fernando (Iberian Conference on Information Systems and Technologies (Print), 2014)
The article tries to track broadly historical evolution of the optimization models of the distribution in plant or layout in order through his historical analysis of trends and recognize the different needs that caused a development of the subject over time.